79th Annual Convention California State Grange - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Portrait of attendees of the 79th Annual Convention California State Grange, in front of the San Jose Civic Auditorium. The front row of a large number of Grange members are wearing regalia.